2020
DOI: 10.1364/ao.393072
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optical time-domain reflectometer with low overhead

Abstract: This paper introduces an integrated optical time-domain reflectometry (iOTDR) design with low overhead based on several innovations, such as analog-to-probability conversion and probability density modulation, as well as well-known techniques. Due to the small form factor, low overhead, and CMOS compatibility of the proposed system, it holds the promise to be integrated with any optical communication transceiver. The prototyping system clearly demonstrates the feasibility of the proposed instrumentation by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…PDM techniques compare the same input voltage against differing references, modulating the equivalent probability density function (pdf). As previously reported, a resistorcapacitor (RC)-based circuit can be used to generate pdf modulation signals [7], [12]. However, this approach requires the use of several circuit components outside the IC chip, adding necessary hardware to the system and disqualifying it as a fully reconfigurable iTDR.…”
Section: B Jitter-based Pdmmentioning
confidence: 99%
See 1 more Smart Citation
“…PDM techniques compare the same input voltage against differing references, modulating the equivalent probability density function (pdf). As previously reported, a resistorcapacitor (RC)-based circuit can be used to generate pdf modulation signals [7], [12]. However, this approach requires the use of several circuit components outside the IC chip, adding necessary hardware to the system and disqualifying it as a fully reconfigurable iTDR.…”
Section: B Jitter-based Pdmmentioning
confidence: 99%
“…A more recent approach described by Xu et al [7] and Mauldin et al [12] uses an analog-to-probability conversion (APC) concept to measure the signal in noisy environments using a differential digital I/O. However, this technique is limited by the offset voltage and hysteresis of the differential receiver/comparator [13].…”
mentioning
confidence: 99%
“…In this paper, we provided the physical model describing the mechanisms of the occurrence of the Rayleigh backscattering patterns and experimentally demonstrated that these patterns can be processed via Optical Time Domain Reflectometry (OTDR) [ 19 ]. Recent advances in the field of OTDR technology [ 20 ] make it promising for practical implementation in the fiber authentication. Although conventional OTDR devices have worse spatial resolution than OFDR, they allow measurements over significantly longer distances and are limited only by attenuation in the waveguide.…”
Section: Introductionmentioning
confidence: 99%